Razumevanje etničnih konfliktov v Srednji Evropi - Ingrao, Charles W. (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2004)
The fifteen years since the fall of Communism have witnessed a plethora of civil wars and rebellions throughout the world that have made many among us nostalgic for the days of the Cold War. But the reasons for these conflicts have less to do with the fall of Communism than with the problems of sustaining harmony within multiethnic societies. These conflicts demonstrate not only that the Wars of Yugoslav Succession were hardly unique, but suggest that the region is more representative of the world at large than the more ethnically homogenous democracies of western Europe and North America. This essay discusses a series of factors in central Europe's historical developmentthat explain its turbulent twentieth-century experience. If there is a "first cause" to the region's distinctiveness from western Europe, it is its maintenance of less tightly centralized governmental forms that helped sustain linguistic and cultural diversity at a time when the great power rivals in the West were imposing uniformity of language, religion and culture.The massive population movements generated by the Habsburg-Turkish wars created even greater ethnic variegation. The Balkan Wars and World War I marked the triumph of the nation-state, but according to a three-tiered hierarchy of peoples that has guaranteed 75 years ofregional instability. The biggest losers were the Jews and Muslim Slavs, who were fated to be distrustedminorities no matter where they lived. The Nazis furthered the nation-state agenda, often by drawing new borders that more closely coincided with existing ethnic frontiers. Yet the horrific record of the Axis regimes mandated a return to the punitive borders of 1919. Whereas a half-century of Communism did at least relieve central Europe's ethnic tensions, its failure as an economic system prompted ruthless politicians like Ceaucescu, Zhivkov and Milosevic to distract their restive peoples by reviving the quest for ethnically homogenous nation states. By the end of the century well over thirty million civilians have been expelled or executed, including the great majority of the region's Jews and Germans.
Keywords: Central Europe; Srednja Evropa; etnične skupine; narodne manjšine; etnični odnosi; etnični konflikti